Update on the pathogenesis and genetics of Paget’s disease of bone - Gennari, Luigi; Rendina, Domenico; Merlotti, Daniela; Cavati, Guido; Mingiano, Christian; Cosso, Roberta; Materozzi, Maria; Pirrotta, Filippo; Abate, Veronica; Calabrese, Marco; Falchetti, Alberto (Frontiers in Cell and Developmental Biology, 2022)
Epidemiological and genetic studies have both shown a strong contribution in individual and family susceptibility to develop Paget's disease of the bone (PDB). In this regard, germline mutations of different genes have been identified, as a possible cause, in affected PDB subjects over the past 20 years and most of the underlying pathways are implicated in the regulation of osteoclast differentiation and function, whereas other are involved in cell autophagy mechanisms. In particular, about 30 different germline mutations of the Sequestosome 1 gene (SQSTM1) have been described in a significant percentage of familial and sporadic PDB cases. The majority of SQSTM1 mutations affect the ubiquitin-binding domain of the protein and are associated to a more severe clinical expression of the disease. Also, germline mutations in the ZNF687 and PFN1 genes have been associated to severe, early onset, polyostotic PDB with increased susceptibly to neoplastic degeneration, particularly giant cell tumor. Mutations in the VCP (Valosin Containing Protein) gene cause the autosomal dominant syndrome "Inclusion Body Myopathy, PDB, Fronto-temporal Dementia", characterized by pagetic manifestations, associated with myopathy, amiotrophic lateral sclerosis and fronto-temporal dementia. Moreover, germline mutations in the TNFRSF11A gene, which encodes for RANK, were associated with PDB and related syndromes. Of interest, genome wide association studies performed in unrelated PDB individuals have identified other potential genes and loci enabling the predisposition to develop the disease. Thus, it is likely that polygenic factors are involved in the PDB pathogenesis in many individuals and that modifying genes may contribute in refining the clinical phenotype. Moreover, the contribution of somatic mutations of SQSTM1 gene and/or epigenetic mechanisms in the pathogenesis of skeletal pagetic abnormalities and eventually neoplastic degeneration, cannot be excluded. Indeed, clinical observations indicate that genetic susceptibility might not be a sufficient condition for the clinical development of PDB without the concomitant intervention of viral infection, in primis paramixoviruses, and/or other environmental factors, such as toxins, calcium and vitamin D assumption in the childhood and tobacco exposure. This review summarizes the most important advances that have been made in the field of cellular and molecular biology PDB over the past decades.